Peningkatan Kemampuan Membaca Al-Qur’an Melalui Metode Tilawati Dalam Perspektif Teori Behavioristik - Ahmad Nur Sholahuddin; Dewi Kurniawati; Kusnul Qomariati; Tri Setyo (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2026)
The purpose of this study is to examine and describe the improvement of students’ ability to read the Qur’an through the implementation of the Tilawati method from a behavioristic learning theory perspective.The methodology used is field research with a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and then analyzed using content analysis techniques. The results and discussion indicate that the implementation of the Tilawati method is carried out systematically through both classical and individual approaches, utilizing the rost melody and repetitive exercises as reinforcement. This method has proven to improve students’ ability to recognize hijaiyah letters, pronounce makharijul huruf correctly, and read the Qur’an more fluently and accurately (tartil). In addition, students show positive responses and higher learning motivation. From a behavioristic perspective, the learning process reflects the presence of stimulus, response, and reinforcement that effectively shape good and correct Qur’an reading habits. The implication of this study shows that the Tilawati method can be used as an effective and practical alternative learning strategy to improve students’ Qur’an reading skills and can be adapted to other Islamic educational institutions with similar conditions.